Comment favoriser le développement de l’activité d’enseignants en prise avec la question du bien-être animal en élevage ? - Amélie Lipp; Laurence Simonneaux (Recherches en Éducation)
Animal husbandry teachers are triggering acute challenges when they plan and realize teaching-learning situations particularly because of the current deep changes in the agricultural domain (environmental impacts of animal breeding, ethical issues, public health...). Our study aims to analyze the potential development of the power to act of animal husbandry teachers when they deal with a learning object such as animal welfare. It is based on an interventionist research conducted with three animal husbandry teachers in bovine husbandry. This article focuses specifically on our choice to articulate two complementary conceptual and methodological frameworks, the didactics of socially acute questions (Simonneaux and Legardez, 2011) and clinic of activity (Clot, 1999) to make comprehensible the potential development of teachers’ power of act. Our results show that the introduction of acute dimensions of animal welfare in the research-intervention methodology allows teachers to describe what is difficult to say or to do in the professional genre. Indeed, the tensions in the teachers’ activity are linked with the professional genre of breeders and the professional genre of teachers. Our results highlight a development of teachers’ power to act supported by an improvement of their action efficiency.